HOW TO PULL TYPES OF DISCRETION OUT OF KELSEN’S PURE THEORY OF LAW - ESCHER, ANA (Pravni zapisi, 2019)
The expression hat-trick (signifying the scoring of three consecutive goals by one player) is very common in sports. In this short paper, coining the legal use of the expression, I will try to pull (3) types of discretion out of Hans Kelsen’s Pure Theory of Law.. Kelsen mentions discretion only in passing. While organizing the loose references to the topic I will analyze whether it can be said that an actual Kelsenian concept of discretion exists. Here, the focus will be on three textual moments in which discretion relevantly appears in Kelsen’s Pure Theory of Law. These three moments, I will argue, can be connected to three types of discretion.   Key words: Hans Kelsen, Pure Theory of Law, Discretion, Determinability, Norm Conflict, Legal Gap.